HOW DO YOU KNOW IF A CHILD HAS AN AUTISM SPECTRUM DISORDER (Conference Zone, 2022)
All over the world, the problem of autism is already widely discussed and successfully solved, and in Russia, unfortunately, there is practically no information about this disease. Although every year the number of children with autism increases exponentially. Pediatricians are very ill-informed about this disease. Years pass before a correct diagnosis is made and treatment begins. Children in our country undergo the first examination by a psychiatrist only at the age of three and only with the consent of their parents, and the first signs of autism are visible much earlier.